Effect of ease of use perception on user interest with attitude as mediator: A case study of Tokopedia users in Klungkung - Ni Kadek Evitasari; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Review of Management, Accounting, and Business Studies, 2024)
This study aimed to determine the influence of the perception of ease of use on user interest with usage attitude as a mediating variable in Tokopedia e-commerce. The population in this study consisted of all Tokopedia e-commerce users in Klungkung Regency. The sample was selected using a purposive sampling technique, resulting in a sample size of 90 people. Data collection was conducted through Google Forms, and the data analysis technique employed SEM-PLS. The results of the study showed that the perception of ease of use had a positive and significant effect on interest in using Tokopedia e-commerce. The perception of ease of use also had a positive and significant effect on the attitude toward using Tokopedia e-commerce. Usage attitudes had a positive and significant effect on interest in using Tokopedia e-commerce. Additionally, the perception of ease of use had a positive and significant effect on interest in using Tokopedia e-commerce through usage attitude as a mediating variable. This research was expected to contribute in the form of suggestions or inputs to interested parties as a consideration for decision-making in addressing problems related to declining user interest.